Photochemical transformation of residential wood combustion emissions: dependence of organic aerosol composition on OH exposure - A. Hartikainen; P. Tiitta; P. Tiitta; M. Ihalainen; P. Yli-Pirilä; J. Orasche; H. Czech; H. Czech; H. Czech; M. Kortelainen; H. Lamberg; H. Suhonen; et al. (Atmospheric Chemistry and Physics, 2020)
Residential wood combustion (RWC) emits large amounts of gaseous and particulate organic aerosol (OA). In the atmosphere, the emission is transformed via oxidative reactions, which are under daylight conditions driven mainly by hydroxyl radicals (OH). This continuing oxidative ageing produces secondary OA and may change the health- and climate-related properties of the emission. However, it is not well known how the composition of RWC-originated OA changes as the function of OH exposure. In this work, emissions from two modern residential logwood combustion appliances were photochemically aged in an oxidation flow reactor (OFR) with various OH exposure levels, reaching up to 6×1011 s cm−3 (equivalent to 1 week in the atmosphere). Gaseous organic compounds were analysed by proton transfer reaction time-of-flight mass spectrometry (PTR-ToF-MS), while particulate OA was analysed online by a high-resolution soot particle aerosol mass spectrometer (SP-HR-ToF-AMS) and offline by in situ derivatization thermal desorption–gas chromatography–time-of-flight mass spectrometry (IDTD-GC-ToF-MS). Photochemical reactions increased the mass of particulate organic carbon by a factor of 1.3–3.9. The increase in mass took place during the first atmospheric equivalent day of ageing, after which the enhancement was independent of the extent of photochemical exposure. However, ageing increased the oxidation state of the particulate OA linearly throughout the assessed range, with ΔH:C/ΔO:C<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="2601598bb742a1df583024dbe1df0bc5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-6357-2020-ie00001.svg" width="72pt" height="14pt" src="acp-20-6357-2020-ie00001.png"/></svg:svg> slopes between −0.17 and −0.49 in van Krevelen space. Ageing led to an increase in acidic fragmentation products in both phases, as measured by the IDTD-GC-ToF-MS for the particulate and PTR-ToF-MS for the gaseous phase. For the gaseous organic compounds, the formation of small carbonylic compounds combined with the rapid degradation of primary volatile organic compounds such as aromatic compounds led to a continuous increase in both the O : C and H : C ratios. Overall, the share of polycyclic aromatic compounds (PACs) in particles degraded rapidly during ageing, although some oxygen-substituted PACs, most notably naphthaldehydic acid, increased, in particular during relatively short exposures. Similarly, the concentrations of particulate nitrophenols rose extensively during the first atmospheric equivalent day. During continuous photochemical ageing, the dominant transformation mechanisms shifted from the initial gas-phase functionalization/condensation to the transformation of the particulate OA by further oxidation reactions and fragmentation. The observed continuous transformation of OA composition throughout a broad range of OH exposures indicates that the entire atmospheric lifetime of the emission needs to be explored to fully assess the potential climate and health effects of RWC emissions.